Radiographic Study on Branching Pattern of the Brachial Artery in Goat - Kumar, Aditya (Indian Journal of Veterinary Anatomy, 2019)
The brachial artery was the continuation of the axillary artery after the origination of the cranial circumflexÂ artery of humerus distal to the shoulder joint. The brachial artery continued on the medial aspect of the arm andÂ gave rose to deep brachial, collateral ulnar, bicipital, transverse cubital, articular, deep antebrachial and commonÂ interosseous artery and continued as the median artery in the forearm region.